A critique of celebrity culture in the field of contemporary musical theatre - Pretorius, Michelle Hester (My University, 2020)
This thesis explores the increasing influence that celebrity culture has on the field of musical theatre, with specific reference to the influence of reality TV on both the audiences of, and performances within, musical theatre. It includes a survey of over 100 years of celebrity casting in musical theatre honing in to focus on two specific performers in one role each, Rachel Tucker in Wicked and Sarah Harding in Ghost. Chapter 1 draws on John Kenrick’s account of musical theatre as a historical artform in Musical Theatre: A History as a basis to explore the changing nature of celebrity casting in musical theatre. This is primarily explored through the construction and analysis of two databases covering 1341 cases of celebrity and star casting since the end of the nineteenth century. This chapter reveals the significant influence of reality TV celebrities on musical theatre in the twenty-first century and focuses on the changing nature of celebrity itself. Chapter 2 relies on the research of P. David Marshall who highlights three main concerns regarding the construction of celebrity within popular culture, to wit identity and individualism, identification by an audience and transformation. An analysis of the presentational and representational media by which the celebrity of two contemporary musical theatre performers is constructed, highlights and relies on these three features. The work of both Erving Goffman and José van Dijck are referred to in the investigation of presentational media, and that of Graeme Turner in the account of representational media. The cultural status of musical theatre and, by extension, the statuses of performers and fans or audience members is explored in Chapter 3 in order to determine the effect the cultural status of the celebrity system and its fans has on musical theatre. The work of Holt N. Parker and John Fiske on high and popular culture and how these function in terms of capital, is also discussed in the third chapter. Chapter 4 identifies four main complicating factors arising from the audience reception of celebrities performing in musical theatre. For this chapter I draw on Michael Quinn’s article, “Celebrity and the Semiotics of Acting”, and Marvin Carlson’s The Haunted Stage, as well as Caroline Heim’s research on the twenty-first century audience, in order to gain a better understanding of these complications that celebrity casting has recently brought to the theatre in the twenty-first century. The aims of each of these chapters are explored through both qualitative and quantitative approaches, conducted through thematic analysis of social media discourse and online surveys regarding the two, previously mentioned, particular cases of celebrity casting in musical theatre. The conclusions drawn from the analysis of these two cases thus reflect the value and problems of twenty-first century celebrity casting in musical theatre
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020